The mechanism of oxytocin and its receptors in regulating cells in bone metabolism - Feixiang, Liu; Yanchen, Feng; Xiang, Li; Yunke, Zhang; Jinxin, Miao; Jianru, Wang; Zixuan, Lin (Frontiers in Pharmacology, 2023)
Oxytocin (OT) is a neuropeptide known to affect social behaviour and cognition. The epigenetic modification of oxytocin receptor (OTR) via DNA methylation not only stimulate parturition and breast milk secretion, inhibit craniopharyngioma, breast cancer, ovarian cancer growth significantly, but also directly regulate bone metabolism in their peripheral form rather than the central form. OT and OTR can be expressed on bone marrow mesenchymal stem cells (BMSCs), osteoblasts (OB), osteoclasts (OC), osteocytes, chondrocytes, and adipocytes. OB can synthesize OT under the stimulation of estrogen as a paracrine-autocrine regulator for bone formation. OT/OTR, estrogen, and OB form a feed-forward loop through estrogen mediation. The osteoclastogenesis inhibitory factor (OPG)/receptor activator of nuclear factor kappa-B ligand (RANKL) signaling pathway is crucially required for OT and OTR to exert anti-osteoporosis effect. Downregulating the expression of bone resorption markers and upregulating the expression of the bone morphogenetic protein, OT could increase BMSCs activity and promote OB differentiation instead of adipocytes. It also could stimulate the mineralization of OB by motivating OTR translocation into OB nucleus. Moreover, by inducing intracytoplasmic Ca2+ release and nitric oxide synthesis, OT could regulate OPG/RANKL ratio in OB and have a bidirectional regulatory effect on OC. Furthermore, OT could increase the activity of osteocytes and chondrocytes, which helps to increase bone mass and improve bone microstructure. This paper reviewed recent studies on OT and OTR in regulating cells in bone metabolism as a reference for their clinical use and research based on their reliable anti-osteoporosis effects.